Acid-fast bacilli in pleural fluid cytology: A rare finding - Garima Agarwal,; Natasha Singh,; Samriddhi Allhabadi,; Suparna Dubey,; Gaurav Garg, (Indian Journal of Case Reports, 2021)
Pleural effusion results from excess fluid production or decreased absorption or both. Tuberculous (TB) pleural effusion is one of the most common forms of extrapulmonary TB. Here, we present the case of a 25-year-old female who presented with chest pain, fever, and decreased appetite from the past 5 months. Her X-ray showed fluid deposition in the lungs. Pleural fluid was sent for cytological examination, 4–5 smears were made and stained with Giemsa, H and E, and acid-fast bacilli (AFB) stain to rule out the tubercular cause of the pleural effusion. Cytological smears were full of degenerated and intact neutrophils. Ziehl–Neelsen stain showed the presence of AFB. However, Mycobacterium tuberculosis is rarely observed on direct examination by AFB staining in pleural fluid. The patient was started with antitubercular drugs and there was a significant improvement in the symptoms of the patient.